Study on Wave Buoy Legged Spider Power Device - Koto, Jaswar; A, Priyanto; A., Maimun; M., Zamani; A.S.A, Kader (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
This paper studied on Wave Buoy Legged Spider power device, a floating wave energy system based on linear generator. The device contains horizontal cylinders arranged such that it looks like the legs of a spider. Inside cylinders will be equipped with a linear generator. During wave motions, some rotors of the linear generators slide forward and backward, thus generating electricity. As a case, a conceptual design of the Wave Buoy Legged Spider device using floating balls of Malaysian wave buoy for an ocean site in Terengganu, West Malaysia is presented. The wave energy was approximately assessed based on observed wave data. Furthermore a method to determine the directional wave spectra by using nonlinear programming has been proposed with introducing a correction factor in order to avoid the concentration of power spectral density. The capability of this method has been verified by the analysis with the data of the experiments of the floating ball response.